Genetic Variability as a Regulator of TLR4 and NOD Signaling in Response to Bacterial Driven DNA Damage Response (DDR) and Inflammation: Focus on the Gastrointestinal (GI) Tract - Spanou, Evagelia; Kalisperati, Polyxeni; Pateras, Ioannis S.; Papalampros, Alexandros; Barbouti, Alexandra; Tzioufas, Athanasios G.; Kotsinas, Athanassios; Sougioultzis, Stavros (Frontiers in Genetics, 2017)
The fundamental role of human Toll-like receptors (TLRs) and NOD-like receptors (NLRs), the two most studied pathogen recognition receptors (PRRs), is the protection against pathogens and excessive tissue injury. Recent evidence supports the association between TLR / NLR gene mutations and susceptibility to inflammatory, autoimmune and malignant diseases. PRRs also interfere with several cellular processes, such as cell growth, apoptosis, cell proliferation, differentiation, autophagy, angiogenesis, cell motility and migration, and DNA repair mechanisms. We briefly review the impact of TLR4 and NOD1/NOD2 and their genetic variability in the process of inflammation, tumorigenesis and DNA repair, focusing in the gastrointestinal tract. We also review the available data on new therapeutic strategies utilizing TLR /NLR agonists and antagonists for cancer, allergic diseases, viral infections and vaccine development against both infectious diseases and cancer.